Karakteristik Komposit Bioplastik Pati Umbi Talas (Colocasia esculenta) dan Karagenan pada Variasi Rasio Bahan Baku dan Konsentrasi Bahan Penguat - Yanthi, Ni Kadek Vira Purnama; Hartati, Amna; Wiranatha, A. A. P. A. Suryawan (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2022)
Bioplastic is one type of plastic that can be degraded naturally because it uses organic materials. This purpose of this study is to determine the effect and interaction of variations in the ratio of raw materials and concentration of reinforcing materials on the characteristics of the bioplastic composites of taro tuber starch (Colocasia esculenta) and carrageenan as well as to determine variations in the ratio of raw materials and concentrations of reinforcing materials in the manufacture of bioplastic composites of taro tuber starch (Colocasia esculenta) and carrageenan which produces the best bioplastic composites. This study used a Factorial Randomized Block design with two factors, namely the ratio of taro tuber starch: carrageenan which consisted of three levels, namely (25:75; 50:50; 75:25 g) and the concentration of cellulose acetate as a reinforcing agent which consisted of 3 the level of (1.67; 5; 8.33%) of polymeric materials. The treatments were grouped into 3 based on the time of making bioplastics, so that 27 experimental units were obtained. The observed variables were tensile strength, elongation at break, modulus young, swelling, biodegradation and functional groups using FTIR. The obtained data were analyzed for diversity and continued with the Honest Significant Difference test. The results showed that the interaction of variations in the ratio of raw materials and concentration of reinforcing materials had a very significant effect on tensile strength, elongation at break, modulus young and biodegradation but had no significant effected the swelling. The characteristics of bioplastic composites in the variation of the ratio of raw materials and concentration of reinforcing materials produced the best values, the tensile strength of 17.60 MPa, elongation at break of 14.91%, modulus young of 154.80 MPa, swelling of 7.52%, biodegradation for 6 – 8 days and contains hydrocarbon functional groups (-(CH 2 )n), alkenes (C – H), alkanes (C – H), phenols, alcohol monomers, hydrogen bonded alcohols (O – H).